2017
DOI: 10.4025/actascianimsci.v39i2.32832
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>In vitro</i> degradation and gas production of <i>brachiaria</i> grass with levels of biodiesel byproducts

Abstract: ABSTRACT. This study aimed to evaluate the in vitro degradability and gas production in diets containing byproducts from the national biodiesel industry (castor bean, canola, forage radish and black sunflower) replacing Brachiaria grass in four levels (0, 30, 50 and 70%). The inoculum for in vitro incubation was obtained from three fistulated Holstein cows. The experimental design was 4 x 4 factorial completely randomized experimental design consisting of four byproducts and four levels. All byproducts studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…On the other hand, we found that the accumulated methane production for T1 is greater since hour 2, showing a significant effect concerning the other treatments, a trend that remains constant until hour 36. For treatment 2, the methane production begins to decrease after 24 hours, which is because the gas and methane production of soluble fractions of high-quality forages may be higher during the first hours of fermentation (Freire et al, 2017); while silages prepared with greater inclusion of the species T. diversifolia maintained a low methane production. However, from the animal production point of view, it is not convenient to produce silage based on a 100% protein source, given the problems in the low acidification of the medium in the silo and the metabolic problems that could be caused in the animal at the rumen level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that the accumulated methane production for T1 is greater since hour 2, showing a significant effect concerning the other treatments, a trend that remains constant until hour 36. For treatment 2, the methane production begins to decrease after 24 hours, which is because the gas and methane production of soluble fractions of high-quality forages may be higher during the first hours of fermentation (Freire et al, 2017); while silages prepared with greater inclusion of the species T. diversifolia maintained a low methane production. However, from the animal production point of view, it is not convenient to produce silage based on a 100% protein source, given the problems in the low acidification of the medium in the silo and the metabolic problems that could be caused in the animal at the rumen level.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, after oil extraction via solvent, remains a toxic residue, named castor-bean meal, which could be used in animal feeding after being detoxified. After detoxification, alkalinization promoted by calcium hydroxide causes ricin denaturation (Oliveira et al, 2010), castor-bean meal presents 900 ± 26 g kg -1 DM; 340 ± 83 g kg -1 crude protein; 30 ± 1.9 g kg -1 ether extract; 460 ± 72 g kg -1 neutral detergent fiber; 60 ± 4.9 g kg -1 non-fibrous carbohydrates, and 180 ± 64 g kg -1 lignin (Gionbelli et al, 2014;Menezes et al, 2015;Freire et al, 2017). Therefore, detoxified castor-bean meal is an absorbent and protein additive capable of improving the fermentation process in sugarcane silage, reducing gas and effluent losses and raising protein content of silage (Moreira et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%